FINANCIAL STABILITY OF THE ENTERPRISE AS A FUNDAMENTAL FACTOR OF SUCCESSFUL DEVELOPMENT OF BUSINESS - E. Sedova; A. Khrisanfova (Вестник университета, 2019)
The article describes the concept of financial stability and its correlation with other indicators of financial position of the company. The opinions of the Russian and foreign economists on this concept are considered. The article also analyzes the external and internal factors which have an influence on financial stability.